Distortion of long cylinders with small diameters due to axial symmetric cooling. (7th October 2005) - Frerichs, F.; Luebben, Th.; Hoffmann, F.; Mayr, P.
The reduction of distortion during heat treatment is not just a problem of the heat treatment process. All manufacturing steps commencing in the steel mill and ending in the heat treating workshop make a contribution to the distortion potential. Possible reasons for distortion phenomena caused by the manufacturing process are inhomogeneities and asymmetries concerning the distributions of mass, alloying elements, microstructure and residual stresses. This paper reports about investigations concerning distortion during heat treatment of long cylinders with small diameters (Ø 20 mm, length 200 mm). Changes in both dimension and shape are taken into account. For a separation of geometrical changes due to pure thermal strain from those with phase transformations, two types of materials were chosen. The first material was the case hardening steel SAE 5120 (EN 20MnCr5). For comparison, the austenitic steel SAE 30300 (German grade X8CrNiS18.9), which shows no phase transformations in the temperature range between room temperature and 900°C, was chosen.